2011
DOI: 10.1523/jneurosci.0187-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Otx2 Promotes the Survival of Damaged Adult Retinal Ganglion Cells and Protects against Excitotoxic Loss of Visual AcuityIn Vivo

Abstract: Retinal ganglion cells (RGCs) are the projection neurons from the eye to the brain and their loss results in visual impairment in a number of diseases. Transcription factors with a homeodomain can translocate between cells and, in at least one reported case, can stimulate neuronal survival. Otx2 is a homeoprotein transcription factor expressed in the retina that is taken up by RGCs. We thus hypothesized that Otx2 capture could regulate the survival of adult RGCs. We report that Otx2 stimulates the survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 35 publications
(51 reference statements)
5
86
0
Order By: Relevance
“…Similarly, Otx2 may function as a survival factor for mDA neurons in the VTA 35,36 that are relatively spared in En1 +/-En2 +/+ mice and less dependent on En1 expression. One can imagine using exogenous Otx2 to rescue VTA mDA neurons, an approach validated in a mouse model of glaucoma 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Otx2 may function as a survival factor for mDA neurons in the VTA 35,36 that are relatively spared in En1 +/-En2 +/+ mice and less dependent on En1 expression. One can imagine using exogenous Otx2 to rescue VTA mDA neurons, an approach validated in a mouse model of glaucoma 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a direct interaction can be observed in the absence of this conserved domain, as shown for Engrailed-1, in which punctual mutations in another domain abolish its ability to bind eIF4E and to regulate mRNA translation (Nedelec et al, 2004;Stettler et al, 2012). Finally, a regulation of the chromatin structure is possible, based on our unpublished observation that some effects of Otx2 and Engrailed can last for several weeks and even months in the models of pathologies that we have developed (Alvarez-Fischer et al, 2011;Torero Ibad et al, 2011). …”
Section: Conclusion: the Future Of Homeoprotein Transductionmentioning
confidence: 81%
“…One of the main models to induce RGC cell death in the retina is the injection of NMDA, which induces RGC apoptosis and necrosis through the secretion of TNF by Mueller Glia cells (Barnett et al, 2009;Lebrun-Julien et al, 2009). In a recent study, we demonstrated that Otx2 injected in the eye at nanomolar concentrations fully antagonizes RGC cell death induced by NMDA and preserves visual acuity (Torero Ibad et al, 2011) (Fig. 10A).…”
Section: Therapeutic Homeoproteinsmentioning
confidence: 90%
See 1 more Smart Citation
“…Still in the context of Otx2 and eye pathology, a mouse model of glaucoma was developed based on the injection of N-methyl-D-aspartate in the eyecup leading to RGC death. The injection of low amounts of Otx2 (between 3 and 30 ng of the protein) is sufficient to prevent RGC death and to maintain normal visual acuity in the optomoter test [24]. A single injection induces long-lasting Otx2 effects and parallels the long-lasting behavioural effect of En1/2 after internalization into mDA neurons suggesting that these two HPs can be considered as therapeutic proteins, at least in mouse models of two human diseases.…”
Section: Engrailed1/2 Influences Mitochondrial Functionmentioning
confidence: 99%